Wiersz o jesieni. O Frantzu François Ozona - Kozłowski , Krzysztof (Przestrzenie Teorii, 2019)
Kozłowski Krzysztof, Wiersz o jesieni. O Frantzu François Ozona [A Poem on Autumn. Frantz by François Ozon]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 77–92. ISSN 1644-6763. DOI 10.14746/pt.2019.32.3. The film Broken Lullaby ([1932] Ernst Lubitsch) and the novel L’Homme que j’ai tué ([1921, 1925, 1930] Maurice Rostand) are seen to be the main inspirations for Frantz (2016) by François Ozon. On the basis of methodology broadly understood as the concept of bringing into relief (Domański, 1992, 2002), this article aims to demonstrate the means by which the French director expanded upon the literary-film material, imbuing it with a totally singular meaning. Ozon’s inventiveness did not limit itself to transformations typical for adaptations, but ventured towards feature film understood as a synthetic work of art that by exploiting the audiovisual properties of the medium itself, acts as a unifying force of poetry (Verlaine, Banville), music (Chopin, Debussy) and painting (Manet). The famous poem recited by the heroine, Ann, Chanson d’automne (Paul Verlaine), serves as the analytical starting point for the above. It is thus used as a pivot for the entire film, a veritable lodestar for guiding motifs, allowing important aspects of the film to be highlighted and consequently, bring its main theme to the fore.